2020
DOI: 10.1007/s11356-020-08693-5
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of European publications between 2001 and 2016 on concentrations of selected elements in mushrooms

Abstract: This article presents a bibliometric study of 200 European publications released between 2001 and 2016, about the contamination of mushrooms by selected elements. The analysis includes figures on the type of analyte, its concentration, the species of fungi, and its country of origin. In the literature review, 492 species of mushrooms (wild-growing and cultured) found in 26 European countries and their concentration of 74 associated elements were analysed. The papers, which dealt mainly with the heavy metal (Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 196 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…41.7% for A. polytricha) and 3.0% (max. 4 . Such juxtaposition clearly shows that the studied mushrooms, both cultivated and wild-growing, can only be considered as an additional, supplemental source of minerals such as K, Cu, Fe, and Zn, but cannot serve as the primary source of their delivery in the human diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41.7% for A. polytricha) and 3.0% (max. 4 . Such juxtaposition clearly shows that the studied mushrooms, both cultivated and wild-growing, can only be considered as an additional, supplemental source of minerals such as K, Cu, Fe, and Zn, but cannot serve as the primary source of their delivery in the human diet.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable interest in mushrooms due to their taste, nutritional value as well as potential risks associated with their consumption [1][2][3][4]. The vast majority of these studies focus on one or several years, during which sporocarps were collected for the purpose of investigating the content of macro-and/or trace elements [5].…”
Section: Introductionmentioning
confidence: 99%
“…Zsigmond et al 18 obtained similar results who examined the inorganic composition of many mushrooms, among which the species L. deliciosus, and the obtained results are similar to results of this study, except that the concentration of aluminum in the cap (52.4 mg kg -1 ) is higher than in the stipe (31.3 mg kg -1 ). Sarikurkcu et al 20 reported lower concentrations of Al in L. sanguifluus (63 mg kg -1 DW). 19 According to the literature analysis, provisional tolerable weekly intake (PTWI) was determined most frequently, but the Joint FAO/WHO Expert Committee on Food Additives (JECFA) gives tolerable intake levels for contaminants, expressed on either a daily or a weekly basis.…”
Section: O N L I N E F I R S Tmentioning
confidence: 97%
“…19 According to the literature analysis, provisional tolerable weekly intake (PTWI) was determined most frequently, but the Joint FAO/WHO Expert Committee on Food Additives (JECFA) gives tolerable intake levels for contaminants, expressed on either a daily or a weekly basis. 20 In view of the cumulative nature of aluminium in the organism after dietary exposure, the Panel considered it more appropriate to establish a tolerable weekly intake (TWI) for aluminium rather than a tolerable daily intake (TDI) and based on the combined evidence from the abovementioned studies, the Panel established a TWI of 1 (mg aluminium/kg bw)/week. 21 If 70 kg is taken as the consumer's average weight, the TWI for aluminium is 70 mg per week.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…A recent article analyzed 200 European publications (published between 2001 and 2016) that describe the concentration of selected elements in mushrooms [ 36 ]. Papers dealing with elements such as Cd, Cu, Fe, Pb, and Zn originated primarily from Turkey, Poland, Spain, and the Czech Republic.…”
Section: Fungal Uptake Of Metals/metalloids With Neurotoxic Potentmentioning
confidence: 99%